Effects of food availability on growth performance and immune-related gene expression of juvenile olive flounder (Paralichthys olivaceus). Issue 80 (September 2018) - Lee, Seunghyung; Lee, Young Mee; Kim, Kyung-Hee; Kim, Hyun Chul; Park, Choul-Ji; Park, Jong-Won; Noh, Gyeong Eon; Kim, Woo-Jin; Hwang, Hyung-Kyu
Abstract: Unfavorable environmental conditions and inappropriate culture practices have increased the vulnerability of cultured fish to disease infection. Up to date many studies have aimed to determine a feeding regimen to maximize productivity; however, very little information on immune responses of cultured fish in response to underfeeding or overfeeding is available. Therefore, a preliminary study was conducted to evaluate effects of graded feeding levels (i.e., food availability) on growth performance and immune-related gene expression of juvenile olive flounder ( Paralichthys olivaceus ). Six different feeding rates including 1, 4, 7, 10, 13, and 16% body weight per day (BW/d) were randomly assigned to three replicate tanks stocking 150 fish (average initial body weight: 0.27 ± 0.02 g; mean ± SD) per tank. A feeding trial lasted for two weeks. Based on the results of the weight gain, nutrient gain, and whole-body compositions and energy content, the feeding rate of 10%, 13%, and 16% BW/d resulted in high nutritional status, whereas the feeding rate of 1% and 4% BW/d resulted in low nutritional status. Intermediate nutritional status was observed at the feeding rate of 7% BW/d. In the given rearing conditions the optimum feeding rate resulting in the maximum growth was estimated to be 11.9% BW/d based on the quadratic broken-line regression model, chosen as the best-fit model among the tested models. Expression of immune-related genes including IL-8 and IgM was significantly down-regulated in the flounder fed at 1% BW/d in comparison to those fed at 7% BW/d. Interestingly, expression of these genes in the flounder fed at 10%, 13%, and 16% BW/d was relatively down-regulated in comparison to that of the flounder fed at 7% BW/d. Although no statistical difference was detected, overall response patterns of other immune-related genes, including TLR3, polymeric Ig receptor, lysozyme C-type, GPx, SOD, and Trx followed what IL-8 and IgM exhibited in response to the various feeding rates. Given the current challenges in aquaculture of the flounder our findings suggest to prohibit underfeeding or overfeeding (i.e., ad-libitum feeding) when culturing the young flounder. Highlights: The feeding rate (1–16% BW/d) significantly influenced nutritional status. Underfeeding significantly reduces immune-related gene expression (IL-8, IgM). Overfeeding possibly results in down regulation of immune-related gene expression.